MANFAAT HASIL BELAJAR KONTRUKSI POLA BUSANA PADA PEMBUATAN POLA BUSANA KERJA WANITA - Latifah Latifah; Katiah Katiah (Universitas Pendidikan Indonesia, 2016)
Competence making women’s fashion can be used as a benchmark as students readiness to plunge into working world through industry work practice program. The research used survey method. The technique of collecting data using questionnaires. The population in this research is class XI Students of SMK Negri 6 Garut . The sample used is total sample amount to 25 students.. This research disclosed that most of the students know the benefits of making women’s fashion learning result in terms of making women’s fashion, women’s fashion sewing basic competencies, completion of women’s fashion with hand stitching and doing pressing the manufacture of women’s fashion. The conclusion of this research indicate that students are able to take advantage of making women’s fashion learning result become the readiness to follow the industry work practice.